Rancang Bangun Sistem Reservasi Ruangan Menggunakan Near Field Communication (NFC) Berbasis Mikrokontroller - Fadhil, Rahmad; Hersyah, Mohammad Hafiz (JITCE (Journal of Information Technology and Computer Engineering), 2020)
Current technological developments also help in the ordering system. Simplifying the reservation system with information technology is one of the innovations made to help users of the room more easily in booking a room. The system designed consists of hardware and software connected to book a room based on, UID, usage time and to open the door of the room. Hardware includes Arduino Mega, NFC tags, NFC readers, relays, solenoids, buzzers, and LEDs. The software includes a Mysql website and database. The system will store user data, date, shift, length of usage and type of room booked by the user. NFC tags will be used by the customer to open the door to the room by getting closer to the NFC reader. This system aims to facilitate the process of borrowing space without having to undergo a convoluted process.